DOMESTIC SERVITUDE BONDS WITH NO COMMON GROUND RACIALIZED ECONOMIC RELATIONSHIPS IN JIM CROW ERA FILMS - Page, Maura M. (My University, 2017)
Using the films Imitation of Life (1934 and 1959) and Pinky (1949) this capstone explores the "racialized economic relationships" between white women and the African American domestic workers they employed. As each film develops, the nature of these women's relationships shifts, appearing to transcend the prescribed roles of employer/employee. However, it is only a veneer of friendship and sisterhood placed over their economic interdependence. Although these movies have multiple themes, this capstone concentrates on the relationships between the characters that begin their associations as employer/employee: Bea and Delilah, Lora and Annie, Miss Em and Pinky, and Dicey and Miss Em. Reviewing each film by decade, this study will examine the correlations and contradictions to the real world of domestic servitude in America from the mid-1930s through the late 1950s, reinforcing the idea that only a surface bond was possible. In Jim Crow America, white women could expand their circle of friends to include "their" black domestics without truly knowing or understanding the black women who took care of them and their families. Reviewing the decades spanning the 1930s through the 1950s in Jim Crow America reveals that interdependent female racial relationships between white women and their black domestic workers have a bond, but not common ground. Their connection stems from the maternalistic tradition associated with domestic servitude.